Actualization of Contemporary Islamic Education Concepts: A Study of the Thoughts of Sayyid Naquib Al-Attas and Buya Hamka - Noer, Syaifudin (Journal of Modern Islamic Studies and Civilization, 2024)
The crisis of Islamic education, along with other pressing issues, has long been apparent within the Islamic world. According to Al-Faruqi, the education sector is suspected to be experiencing the worst crisis. This should not happen because the spirit of renewal in Islam should not only touch upon political, military, and economic aspects but should also be more focused on education. This type of research is a literature review, utilizing a factual-historical approach concerning prominent figures. Through several efforts, this research concludes that what has been formulated by Al-Attas and Hamka, particularly regarding education, is their intellectual jihad to realize an ideal Islamic education system. This system is based on moral, spiritual, and religious values. The orientation and values of Islamic education fundamentally lie in the harmony and balance of the complete individual, encompassing both the physical and spiritual aspects of human beings. Similarly, when viewed in terms of the human function as the servant of Allah ('abd Allah), symbolizing the vertical dimension, and as the vicegerent on earth (khalifah fi al-ard), symbolizing the horizontal dimension.